Historical bases of the roman law revival and popularization of it by medieval universities - Ivanii Olena (Borys Grinchenko Kyiv Metropolitan University, 2016)
In the offered article the degree of influence of the Western Europe medieval universities on the process of the Roman law revival and popularisation of it are examined. We examine the history of the Roman law formation in the universities of Spain, Germany, France and the role in it of Bologna University as the centre of juridical science in the Medieval Europe. It has been shown that the Roman law, as any other factor of the Middle Ages, contributed to the overcoming of state and other territorial boundaries, to creation of unified organisation of European legal culture, juridical science and education. It has been made the conclusion that the revival of the Roman law studying is the main factor that contributed to the appearing of Roman-Germanic legal family; it is historically those countries where jurists and practice workers were getting juridical education in the universities, were perceiving legal conceptions, views and thoughts of the Roman law, which in the process of time lied in the basis of legislation of all European nations. It was shown that the role of the universities also lied down in the help of defining the transnational character of Western jurisprudence, as during three hundred years (from 1050 till 1350) the whole Europe was the united cultural organism. In the Western Europe countries the juridical thinking and typical juridical practice were formed, that also became the factor that united a lot of nations, the factor of community of their material and spiritual life.